(untitled) (Global Journal of Science Frontier Research, 2024)
The research includes several studies on the behavior of some meadow grasses of local origin which are the result of our selection They are grown either as a monoculture or in a mixture on the slopes of the Central Balkan Mountain in Bulgaria with different exposure to the main directions of the world and a variety of soil gleying The duration of the study is different During the study period in the 10th-13th experimental years a relative equality of productivity by habitat was established with solid and weak soil gleying respectively on the low or high part of the slope especially with eastern and southeastern exposure of the mountain slope The principle of rhythmicity in Nature increase or decrease in productivity in even or odd years fixed in the ancient Bulgarian calendar finds expression in the manifestations of cultivated grasslands Red fescue Festuca rubra L var genuina Gr et Good is the structure-determining component of the grasslands Some understandings are shared about principles in the interrelations between meadow grasses in the community Specific questions of allelopathy as a natural phenomenon are considered The response of some meadow grasses grown in areas weeded with eagle fern was studied